The Effect Of Giving Health Education With Tik Tok Video Media On The Knowledge Of Prevention And Handling Of Children With Pneumonia In The Posyandu Of Mojoroto Village Kediri City - Zainal Andy Saputra; Salva Ayu Vidias Putri; Yuli Peristiowati; Arantrinita; Bayu Prabowo; Hariyono (Universitas STRADA Indonesia, 2025)
Pneumonia is a respiratory disorder that is the leading cause of death for children under five years old worldwide, so prevention is an important component of the strategy to reduce mortality. This study aims to determine the effect of providing health education with tik tok video media on the knowledge of prevention and handling of children with pneumonia. This type of research uses a pre-experimental approach with a one group pre-test post-test design and probability sampling of 99 respondents. This study was conducted on July 15, 2024 using a questionnaire. Health education through TikTok video media is an effective way to provide knowledge. Easy access to media at any time and can be played repeatedly, making a person fully understand the concepts conveyed to improve their cognitive abilities.